Aculturación, transculturación, inculturación en el aula (Educational Perspectives Magazine (REPED), 2022)
Chilean students do not enjoy their schools because they have to leam a culture that does not pertain to their idiosyncrasy. The Chilean system of education prefers to adopt a neutral identity which belongs to general culture and does ignore the processes of culture. Attainment from natural processes or societal environment, so processes like inculturation, acculturation and transculturation are generally ignored by teachers in the classroom. This generates a conflict between students and the teachers in the classroom. This Critical essay suggests that teachers and the general system of education in Chile take into consideration youth culture and incorpórate it in school programmes.